Vaninka : Celebrated Crimes - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2004)
"Vaninka" by Alexandre Dumas is a historical novel likely written in the early 19th century. The story unfolds during the reign of Emperor Paul I of Russia, focusing on themes of social status, power, and the complexities of love amidst the rigid hierarchy of the Russian nobility. The main character, Vaninka, is a proud and beautiful young woman who navigates her relationships with her father, General Count Tchermayloff, and her potential suitor, Foedor Romayloff, set against a backdrop of severe societal constraints and expectations. The opening of "Vaninka" presents a tense scene where a large crowd gathers to witness the public punishment of a serf, Gregory, in front of General Tchermayloff$1 (Bs house. The grim atmosphere is underscored by the aide-de-camp, Foedor, who is eager to glimpse Vaninka from a window, signifying his deep and complicated feelings for her. As the punishment unfolds, the narrative introduces the complex dynamics between the characters$1 (BFoedor, torn between duty and desire, and Vaninka, whose pride and haughty demeanor shape her identity in a world where she enjoys considerable privilege yet harbors romantic aspirations. This powerful introduction sets the stage for Vaninka's tumultuous journey, woven through themes of love, authority, and rebellion against social norms. (This is an automatically generated summary.)s
Release date is 2004-09-22
Produced by David Widger
Keywords: Crime